Health risk assessment of nitrate exposure in well water of residents in intensive agriculture area - Jamaludin, Noraziah; Mohd Sham, Shaharuddin; Syed Ismail, Sharifah Norkhadijah (Science Publications, 2013)
Nitrate in well water has become a public health concern especially in agriculture areas. Nitrate contamination in drinking water poses health risks to humans. This cross-sectional study was conducted with an aim to determine the health risk of residents in intensive agriculture area of Bachok Kelantan from nitrate exposure in drinking well water. Nitrate in well water was determined with Spectrophotometer while the health risk was determined through calculation of Chronic Daily Intake (CDI) and Hazard Index (HI). Results indicate that nitrate level in this study was below the Maximum Concentration Limit of National Drinking Water Quality Standard of Malaysia (NDWQS) (<10 mg L-1) with the Mean ± SD of 1.66±2.11 mg L-1 and range between 0 to 9.60 mg L-1. The highest Mean ± SD of nitrate was determined in Kampung Aman (3.34±4.07 mg L-1). The mean ± SD for CDI was 0.051±0.086 mg kg day-1 and the HI was <1. This indicate the health risk of residents from nitrate exposure in this area were in acceptable range.